Electrochemical Processes for the Formation of Hydroxyapatite Powders - Adrian Nur; Heru Setyawan; Arief Widjaja; I. Wuled Lenggoro (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Electrochemical synthesis of hydroxyapatite particles was performed from a homogeneous solution of Na2H2EDTA.2H2O, KH2PO4 and CaCl2 without stirring to investigate the mechanism of hydroxyapa-tite formation. We found that OH- ions generated by water reduction at the cathode play an important role in the formation of hydroxyapatite particles. The OH- ions induce the liberation of Ca2+ ions and the dissociation of phosphoric acid, which serve as the reactants for the formation of hydroxyapatite particles. Two layers with a clear boundary were formed during electrolysis. The upper layer comprises the produced particles and the lower layer is a homogeneous solution. The produced particles were held in the region between the electrodes mainly due to the electrostatic interactions of charged particles in an electric field. The hydroxyapatite particles are agglomerates consisting of spherical particles. Aging the suspension for 24 h after electrolysis leads to the transformation of hydroxyapatite to brushite. Thus, if producing hydroxyapatite is desired, the particles should be continuously removed from the system. This method appears to be promising as a continuous process to produce hydroxyapatite parti-cles using an electrochemical method. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)